ANALISIS FAKTOR YANG MEMPENGARUHI KONSUMSI MASYARAKAT KABUPATEN KOTA DI PROVINSI SUMATERA UTARA - Bungaran Silalahi; Raina Linda Sari; Irsad Lubis (Journal of Economic, Bussines and Accounting (COSTING), 2026)
This study aims to analyze the factors influencing household consumption levels across regencies/municipalities in North Sumatra Province. The research employs panel data from 33 regencies/municipalities over the period 2021–2024, sourced from Statistics Indonesia (BPS). The dependent variable is household consumption, while the independent variables include GRDP per capita, Regency/Municipality Minimum Wage (UMK), Open Unemployment Rate (TPT), Gini ratio, population size, and dependency ratio. The analytical method applies panel data regression with a model selection procedure, in which the Fixed Effect Model (FEM) is identified as the most appropriate specification. The results indicate that GRDP per capita and the minimum wage exert a positive and statistically significant effect on consumption. The Gini ratio also shows a positive and significant influence, whereas population size has a positive but statistically insignificant effect. Meanwhile, the unemployment rate and dependency ratio demonstrate negative but statistically insignificant effects. The Adjusted R-squared value of 0.965576 indicates a high explanatory power of the model. These findings confirm that economic factors play a more dominant role than demographic factors in shaping regional consumption patterns. Policy implications emphasize the importance of income enhancement, optimization of minimum wage policies, and strengthening human capital quality.